Kesadaran Wajib Pajak, Penggunaan Aplikasi Pagi Denpasar dan Kepatuhan Wajib Pajak Hotel pada Wajib Pajak Restoran - Hermanto, Adinda Shavina Putri; Erawati, Ni Made Adi (E-Jurnal Akuntansi, 2023)
Taxes are levies given to the state by taxpayers and will be used solely for the benefit and welfare of society. As a tourism area, Denpasar City's original regional income cannot be separated from hotel and restaurant tax contributions. This research aims to provide empirical evidence regarding the influence of taxpayer awareness and use of the Pagi Denpasar application on hotel taxpayer and restaurant taxpayer compliance. Attribution Theory and Technology Acceptance Model (TAM) are used in this research. The sample collection method was purposive sampling and the sample in this study was 36 hotels that have restaurant facilities. Data analysis uses multiple linear regression analysis. The influence of taxpayer awareness and use of the Pagi Denpasar application is shown by positive results on hotel taxpayer and restaurant taxpayer compliance. The implications of this research support the theory used and can provide information regarding the influence of taxpayer awareness and use of the Pagi Denpasar application to the wider community. Keywords: Tax; Hotel; Restaurant; Awareness; Compliance.